Attitudes of Soviet Citizens towards State Loans 1946-1957 after their Cancellation (Based on Personal Source Materials) - M. D. Novikov (Научный диалог, 2024)
The article explores the issue of public attitudes of Soviet citizens towards measures of state financial policy. It examines the sentiments of USSR citizens after the cessation of campaigns related to the issuance of government bonds from 1946 to 1957. The primary sources of information were letters from citizens addressed to Soviet government bodies, as well as diary entries. The study relies on methodological achievements in the “history of emotions.” It was revealed that after the abolition of compulsory subscription campaigns for domestic state loans, the key issue became the repayment of the state debt. It is shown that citizens placed high hopes on the revision of decisions by N. S. Khrushchev after his resignation in 1964. Their attempts to engage in dialogue with authoritative structures and leaders were made repeatedly before the official redemption began, but they did not contribute to a review of earlier decisions until 1974. The study demonstrates that the gradual redemption of bonds in the 1970s-1980s contributed to the establishment of a social compromise, and the practice of mass loans transformed from a measure of current financial and social policy into a subject for historical reflection, discussion, and nostalgia.